2007
DOI: 10.1242/jeb.02675
|View full text |Cite
|
Sign up to set email alerts
|

Variation in estradiol level affects cortical bone growth in response to mechanical loading in sheep

Abstract: SUMMARY Although mechanical loading can stimulate cortical bone growth, little is known about how individual physiology affects this response. This study demonstrates that in vivo variation in estradiol (E2)level alters osteoblast sensitivity to exercise-induced strains, affecting cortical bone responses to mechanical loading. Subadult sheep were divided into treatment groups that varied in terms of circulating E2 levels and loading (exercised and sedentary). After 45 days, periosteal cortical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…As compared to the other groups, animals in the latter group grew up to 27% more periosteal bone in response to exercise (Fig. 2), 55 supporting the hypothesis that higher E 2 levels upregulate skeletal responses to exercise. Specifically, this result highlights the point that E 2 may increase the sensi- tivity of bone to mechanical loading, but this has little effect on bone growth unless loading is actually occurring.…”
Section: Do Estrogen-strain Interactions Affect Skeletal Robusticity?supporting
confidence: 70%
See 1 more Smart Citation
“…As compared to the other groups, animals in the latter group grew up to 27% more periosteal bone in response to exercise (Fig. 2), 55 supporting the hypothesis that higher E 2 levels upregulate skeletal responses to exercise. Specifically, this result highlights the point that E 2 may increase the sensi- tivity of bone to mechanical loading, but this has little effect on bone growth unless loading is actually occurring.…”
Section: Do Estrogen-strain Interactions Affect Skeletal Robusticity?supporting
confidence: 70%
“…2). 55 Further, two studies in ovariectomized (OVX) rats reported that a combination of estrogen and mechanical loading protected against OVX-induced bone loss. These studies used a raised-cage model, in which food is placed at a height that requires the animal to use a bipedal stance.…”
Section: Do Estrogen-strain Interactions Affect Skeletal Robusticity?mentioning
confidence: 99%
“…Since the sample was composed of only female individuals from a single inbred strain, variation in hormonal levels (e.g. Devlin and Lieberman, 2007) likely had at most only a minor contribution to shape differences between groups that expose femora to different mechanical loading environments. Similarities in average Ps.Ar and Ct.Ar of groups is consistent with the view that our experimental design eliminated most confounding variables.…”
Section: Effects Of Locomotor Modes On Femoral Morphologymentioning
confidence: 99%
“…Bone curvature is also known to change ontogenetically and in response to applied muscular and gravitational loads (Lanyon, 1980;Richmond, 1998;Jungers et al, 2002;Main and Biewener, 2006), and bone crosssectional properties are also well known to respond to loading conditions during ontogeny (Goodship et al, 1979;Lanyon et al, 1982;Carrier, 1983;Jaworski and Uhthoff, 1986;Haapasalo et al, 1994;Pearson and Lieberman, 2004), although the effects are dependent on many factors including age, hormonal levels, and initial bone status (Forwood and Burr, 1993;Damien et al, 1998;Lee et al, 2003;Lieberman et al, 2003;Ruff, 2003a,b;Devlin and Lieberman, 2007). Although this list is not comprehensive, these studies demonstrate that many aspects of bony morphology respond to bone loading conditions during an animal's lifetime.…”
mentioning
confidence: 99%